2021
DOI: 10.1177/0886260521991271
|View full text |Cite
|
Sign up to set email alerts
|

10-Year Study of Christian Church Support for Domestic Violence Victims: 2005-2015

Abstract: Religious beliefs play a significant role in the lives of victims of domestic violence. Victims find strength in their faith and would rather endure the violence at all costs to keep a family or a marriage together, than to compromise their faith by leaving. This 10 –year study explored the climate of support for victims of domestic violence among Christian clergy and church members between 2005 and 2015. Using a convenience sample, surveys were sent out to congregations in the Upper Midwest in 2005 and 2015. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Faith‐based organizations have been credited as providing critical support to those in family violence situations (de la Rosa, Barnett‐Queen, Messick, & Gurrola 2016; Zust, Flicek, Moses, Schubert, & Timmerman 2018). Churches and other faith‐based institutions provide informal counselling and support as well as community assistance necessary to keep them safe (Fuchsel 2012).…”
Section: Why Family Violence Increases After Disastersmentioning
confidence: 99%
“…Faith‐based organizations have been credited as providing critical support to those in family violence situations (de la Rosa, Barnett‐Queen, Messick, & Gurrola 2016; Zust, Flicek, Moses, Schubert, & Timmerman 2018). Churches and other faith‐based institutions provide informal counselling and support as well as community assistance necessary to keep them safe (Fuchsel 2012).…”
Section: Why Family Violence Increases After Disastersmentioning
confidence: 99%
“…Previous studies have supported this hypothesis, showing that fear of separation or ostracization may cause women to remain in unhealthy relationships. 116 , 117 Second, in some cases, clergy may advise victims to resign themselves to the situation, rather than report it to the police, thus perpetuating the cycle of violence. 118 Third, studies in Eastern cultures have found that both men and women agree that men can beat their partner if she refuses sex or retaliates during a fight.…”
Section: Discussionmentioning
confidence: 99%